1959
DOI: 10.1172/jci103808
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Urinary Ionic Strength on Phosphate Pk2′ and the Determination of Titratable Acid*

Abstract: It is well recognized that the pK' value for the salt of a weak acid or base is significantly influenced by the ionic strength of the solution. In the case of phosphate, the theoretical value for pK2 in an infinitely dilute solution is 7.181 at 370 C. (1) and in a solution of ionic strength comparable to that of plasma is approximately 6.8.The small variations in ionic strength ordinarily encountered in plasma would not be expected to produce significant deviations from this latter value. However, in view of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

1961
1961
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…Urinary ammonium was analyzed by ion chromatography. 38 Titratable acidity in urine was calculated from urinary PO4 excretion, urine pH, and blood pH, with the pK' of PO4 corrected for ionic strength by the method of Schwartz et al 39 Urinary NAE was calculated as ammonium plus titratable acid minus bicarbonate excretion. We measured 1,25(OH) 2 Laboratories, Inc., Minneapolis, MN).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary ammonium was analyzed by ion chromatography. 38 Titratable acidity in urine was calculated from urinary PO4 excretion, urine pH, and blood pH, with the pK' of PO4 corrected for ionic strength by the method of Schwartz et al 39 Urinary NAE was calculated as ammonium plus titratable acid minus bicarbonate excretion. We measured 1,25(OH) 2 Laboratories, Inc., Minneapolis, MN).…”
Section: Discussionmentioning
confidence: 99%
“…PTH was then administered i.v., as in the preceding experiments, and two additional timed urine collections were obtained. Each urine sample was analyzed for pH, CO2 content, ammonium (25), and titratable acid (26). The values in individual animals were averaged before and after PTH administration and analyzed statistically by paired t test.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proposed that excretion of αKG and other organic anions (e.g., citrate) in the urine represents the loss of "potential HCO 3 -," which provides the advantage of minimizing bicarbonaturia under alkali load (6). The latter is important because it allows the excretion of base at a lower urinary pH, thereby diminishing the risk of nephrolithiasis due to the formation of calciumphosphate precipitates [αKG: pKa 1 (1.9), pKa 2 (4.4); bicarbonate: pKa 1 (6.1); HPO 4 2-: pKa 2 (6.7-6.8)] in the urine (5,7). Collectively, these results demonstrated that acid-base status is a major factor determining blood levels of αKG and the rate of αKG excretion into urine.…”
mentioning
confidence: 99%